Iron cycling and stable Fe isotope fractionation in Antarctic shelf sediments, King George Island. (15th September 2018) - Henkel, Susann; Kasten, Sabine; Hartmann, Jan F.; Silva-Busso, Adrián; Staubwasser, Michael
Abstract: Iron (Fe) fluxes from reducing sediments and subglacial environments are potential sources of bioavailable Fe into the Southern Ocean. Stable Fe isotopes (δ 56 Fe) are considered a proxy for Fe sources and reaction pathways, but respective data are scarce and Fe cycling in complex natural environments is not understood sufficiently to constrain respective δ 56 Fe "endmembers" for different types of sediments, environmental conditions, and biogeochemical processes. We present δ 56 Fe data from pore waters and sequentially extracted sedimentary Fe phases of two contrasting sites in Potter Cove (King George Island, Antarctic Peninsula), a bay that is affected by fast glacier retreat. Sediments close to the glacier front contain more easily reducible Fe oxides and pyrite and show a broader ferruginous zone, compared to sediments close to the ice-free coast, where surficial oxic meltwater streams discharge into the bay. Pyrite in sediments close to the glacier front predominantly derives from eroded bedrock. For the high amount of easily reducible Fe oxides proximal to the glacier we suggest mainly subglacial sources, where Fe liberation from comminuted material beneath the glacier is coupled to biogeochemical weathering processes (likely pyrite oxidation or dissimilatory iron reduction, DIR). Our strongest argument for a subglacial source of the highly reactive Fe pool in sediments close to the glacier front is its predominantly negative δ 56 Fe signature that remains constant over the whole ferruginous zone. This implies in-situ DIR does not significantly alter the stable Fe isotope composition of the accumulated Fe oxides. The nonetheless overall light δ 56 Fe signature of easily reducible Fe oxides suggests pre-depositional microbial cycling as it occurs in potentially anoxic subglacial environments. The strongest 56 Fe-depletion in pore water and most reactive Fe oxides was observed in sediments influenced by oxic meltwater discharge. The respective site showed a condensed redox zonation and a pore water δ 56 Fe profile typical for in-situ Fe cycling. We demonstrate that the potential of pore water δ 56 Fe as a proxy for benthic Fe fluxes is not straight-forward due to its large variability in marine shelf sediments at small spatial scales (−2.4‰ at the site proximal to oxic meltwater discharge vs. −0.9‰ at the site proximal to the marine glacier terminus, both at 2 cm sediment depth). The controlling factors are multifold and include the amount and reactivity of reducible Fe oxides and organic matter, the isotopic composition of the primary and secondary ferric substrates, sedimentation rates, and physical reworking (bioturbation, ice scraping). The application of δ 56 Fe geochemistry may prove valuable in investigating biogeochemical weathering and Fe cycling in subglacial environments. This requires, however (similarly to the use of δ 56 Fe for the quantification of benthic fluxes), that the spatial and temporal variability of the isotopic endmember is known and accounted for. Since geochemical data from subglacial environments are very limited, further studies are needed in order to sufficiently assess Fe cycling and fractionation at glacier beds and the composition of discharges from those areas.